Synthesis, characterization and controlled release properties of magnesium aluminium layered double hydroxide 4-chlorophenoxyacetic acid nanocomposite / Nur Suhana Mohd Ali - Mohd Ali, Nur Suhana (Faculty of Applied Sciences, 2017)
Layered double hydroxide (LDH)-based nanohybrid, created by interacting LDH nanocomposite with another nanoparticles, are come out in active area for environmental protection, healthcare, and storage of drugs or herbicides. In this study, Herbicides, 4-chlorophenoxyacetic acid were intercalated into MgAl-layered double hydroxide (LDH) by using molar ratio 2 (R=2). It is synthesised via co-precipitation method at pH 10 (± 0.5). The intercalation compound (MgAl-4CPA), was characterised using PXRD and FTIR-ATR to confirm that guest anion are successfully intercalated into MgAl-LDH nanohybrids. The XRD pattern shows that at concentration 0.7 M, the basal spacing shift from 8.9 Å to 9.3 Å, which means the guest anion was successfully intercalated. The result supported by the FTIR-ATR spectrum that shows nitrate peak at wavenumber 1353.50 cm-1 disappeared and carboxylate ion (COO-) bandpresence at wavenumber 1596.29 cm-1. Meanwhile, the controlled release studyof 4CPA from MgAl-LDH nanohybrids shows that carbonate aqueous salt solution released the percentage of 4CPA higher than tap water, which are 19.72 and 18.92 %, respectively. This study offered that controlled release of 4CPA from LDH can created safer agent of agrochemicals that can be used in agricultural fields.